DAMPAK PEMBELAJARAN DI MASA PANDEMI TERHADAP MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK KELAS XI DI SMK NEGERI 4 MALANG - Muhammad Mustofa; Arief Ardiansyah; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
The Covid-19 pandemic has hit the world, including Indonesia, for the last 2 years or so. Covid-19 has had many impacts, especially on educational institutions. In educational institutions, the learning process carried out during this pandemic period experienced many problems. This makes the Ministry of Education and Culture make a firm policy relating to the implementation of learning during the Covid-19 pandemic to prevent wider transmission. This paper examines educational policies during the Covid-19 pandemic related to the implementation of E-Learning-based learning, where learning that was previously carried out face-to-face (offline) is replaced with online. The E-Learning-based learning process is a solution for implementing education during the pandemic which is still not optimal as a whole. Many still need to be considered in its implementation both in terms of teachers, students, and also learning tools. In terms of teachers still need to improve the quality of teachers in the creativity used during online learning and the use of information technology. During this covid 19 period, PAI teachers at SMK Negeri 4 Malang made new innovations and creativity in online learning by utilizing learning media (technology). Teachers are able to use online learning media, such as using WhatsApp media, Youtube media, Google Classroom media, Google Internet media, Google Meet media, Zoom media, and Power Point.